Long-Term Effect against Methicillin-Resistant Staphylococcus aureus of Emodin Released from Coaxial Electrospinning Nanofiber Membranes with a Biphasic Profile - Ye, Peiwen; Wei, Suying; Luo, Chaohua; Wang, Qirui; Li, Anzhang; Wei, Fenghuan (Biomolecules (Basel, Switzerland), 2020)
Methicillin-resistant Staphylococcus aureus (MRSA) is a serious and rapidly growing threat to human beings. Emodin has a potent activity against MRSA; however, its usage is limited due to high hydrophobicity and low oral bioavailability. Thus, the coaxial electrospinning nanofibers encapsulating emodin in the core of hydrophilic poly (vinylpyrrolidone), with a hygroscopic cellulose acetate sheath, have been fabricated to provide long-term effect against MRSA. Scanning electron microscopy and transmission electron microscopy confirmed the nanofibers had a linear morphology with nanometer in diameter, smooth surface, and core-shell structure. Attenuated total reflection-Fourier transform infrared spectra, X-ray diffraction patterns, and differential scanning calorimetric analyses verified emodin existed in amorphous form in the nanofibers. The nanofibers have 99.38 ± 1.00% entrapment efficiency of emodin and 167.8 ± 0.20% swelling ratio. Emodin released from nanofibers showed a biphasic drug release profile with an initial rapid release followed by a slower sustained release. CCK-8 assays confirmed the nontoxic nature of the emodin-loaded nanofibers to HaCaT cells. The anti-MRSA activity of the nanofibers can persist up to 9 days in AATCC147 and soft-agar overlay assays. These findings suggest that the emodin-loaded electrospun nanofibers with core-shell structure could be used as topical drug delivery system for wound infected by MRSA.